Biodiesel Production from Waste Palm Cooking Oil Using Immobilized Candida rugosa Lipase - Rahmath Abdulla; Eryati Derman; Thivyasri K. Mathialagan; Abu Zahrim Yaser; Mohd Armi Abu Samah; Jualang Azlan Gansau; Syed Umar Faruq Syed Najmuddin (MDPI, 2022)
Biodiesel production from Waste Palm Cooking Oil (WPCO) is of interest to substitute fossil derived diesel fuel, due to its renewable nature, cleaner emissions, and non-toxic properties. Thus, in this study, biodiesel production through transesterification process was optimized using immobilized lipase from Candida rugosa and WPCO collected from the faculty’s cafeteria as a feedstock. Interaction between five operating factors: molar ratio of ethanol to oil, water content, lipase loading, reaction temperature and time on the biodiesel yield were investigated. It was observed that, with the optimal conditions of 10:1 molar ratio of ethanol to oil, 1 g water, temperature 40 ◦C, 0.8 g immobilized lipase and 32 h reaction time, a yield of 85.72% of biodiesel could be achieved. Thus, this study shows that WPCO, an environmental waste, can be utilized as a promising feedstock for biodiesel production using environmentally friendly biocatalysts such as immobilized lipase.